The marginalized in the Ibadi Nawazli heritage: The book “Masa’il Nafusa al-Jabal” by Imam Abd al-Wahhab ibn Abd al-Rahman ibn Rustum (171-208 AH/787-823 AD) as a model - houcine, Nasr al-Din; hasbellaoui, Naseem (The Algerian Historical Journal, 2026)
Jurisprudential novels are among the most important sources of historical writing, as they contain information about different segments of society. They contain valuable information about marginalized groups such as the poor. And thieves; and slaves; And other groups that have been marginalized. Perhaps one of the most important books on disasters that helped to lift the curtain on some of these segments of Ibadi society is the book: "Questions of the Souls of the Mountain," by Imam Abd al-. Wahhab bin Abd al-Rahman bin Rustam. On the basis of this proposal, we will try in this study to discover the most important marginalized groups who were exposed to the issues of the book and the conditions in which they lived without weighing down the jurisprudential text. which takes him out of the field of study.